Role Liquidity for Pay off Short Term Debt - Ilyas Lamuda; Abdul Rahmat; Pravin R. Choube (Global Scientific Publishing, 2023)
Role Liquidity For Pay off Short Term Debt at PT.Mustika Ratu Tb, Research objectives This is For analyze role liquidity in pay off debt period short . Data used deep study This namely quantitative data form report finance. PT.Mustika Ratu Tbk Analysis technique used is method analysis descriptive that is use ratio finance. Research result This based on assessment role liquidity For pay off debt period short during four year with 2018-2021 averages reviewed from The Current Ratio produces an average of 258.42% which is above standard industry , reviewed from Quick Ratio produces an average of 169.43% which is above standard industry, and reviewed from Cash Ratio yielding an average of 7.50% is under standard industry. With so PT. Mustika Ratu Tbk based on analysis Ratio Liquidity showing company capable in fulfil debt period in short, except when repayment with use financial cash company categorized as No capable pay off period short moment due date.
Keywords: Current Ratio; Quick Rati; Cash Ratio